Investigating the Psychometric Properties of the Persian Version of the Massachusetts Youth Screening Instrument (MAYSI-2) - Hashemi, Seyedeh Fatemeh (International journal of offender therapy and comparative criminology, 2023)
This study was done to prepare a Persian version of the MAYSI-2 and investigate its psychometric properties among the adolescents of the Juvenile Correction and Rehabilitation Center in Mashhad. By available study sample 329 male adolescents were selected. The findings showed that the Cronbach’s alpha values for subscales were from .74 to .91. Compound reliability was also obtained in different scales between .72 and .98 indicating the optimal reliability of the scale. The CVR and CVI indicating the appropriate content validity. The results of CFA showed that the factor loading of the items was more than .5. The scale had good structural validity. The GFI of .90, IFI of .91, and RMSEA of .072 were all within the acceptable limits. Convergent and divergent validity indicators showed that the subscales benefited from the convergent validity. Our results showed that the Persian version of the MAYSI-2 had desirable psychometric properties. Therefore, it can be used for assessing mental health problems of juvenile delinquent and upcoming research.